Effects of VEGF Gene Polymorphisms on BEV Responsiveness in a Sample of Iraqi Colorectal Cancers Using HRM - PCR (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Vascular endothelial growth factor (VEGF) have a vital role in the molecular genetic eventsof angiogenesis and vasculogenesis, so it is involved in the development of cancer. Single nucleotidepolymorphisms (SNP) in VEGF gene has been announced as a risk factor in colorectal cancer. Bevacizumab(BEV) is an angiogenesis inhibitor that curb the binding of VEGF to its receptors obstructing the angiogenesisprocess. Objective: The ideal goal of ongoing study lies in revealing the effect of rs699947 (-2578 C/A (andrs833061 (-460C/T( polymorphisms in the promoter of VEGF gene on the development of colorectal cancerand on the BEV responsiveness in a sample of Iraqi patients using High Resolution Melting Analysis (HRM)analysis. Methodology: Venous blood samples were collected from 25 colorectal cancer patients withresponse to BEV treatment and 25 with BEV resistant and 25 apparently healthy individuals as controlgroup who matched with patients in age and gender. Results: AA and CA polymorphisms A allele ofrs699947 (-2578 C/A) and TT and CT polymorphisms and T allele of rs833061 (-460C/T( were representa risk factor on the occurrence of the colorectal cancer. It has been found that CC and CA polymorphismof the VEGF - 2578 C/A and CT genotype of the VEGF -460 C/T polymorphism might be a predictivefactors of responsiveness to BEV chemotherapy in CRC patients. Conclusion: These outcomes confirm theessential role that VEGF polymorphisms play in the occurrence of CRC and the correlation between SNPs inVEGF promoter region and the BEV responsiveness. With this, further research and investigation of VEGFpolymorphisms could allow for its use in identifying risk factors for the development of CRC and increasingits predictive value for anti-VEGF cancer therapies.